Insider/Outsider. My Immigrant Experience as a Photo Artist - Pietropaolo, Vincenzo (Italian Canadiana, 2023)
The question of insider/outsider artist has long been a central concern in my work as a social documentary photographer who practises as a member of the Italian diaspora and, in turn, in the way my work has been received and disseminated by the Other in the context of art criticism and the art gallery establishment. This paper will situate bodies of my photography work that concern immigrant and working-class subcultures in the context of the following theoretical frameworks: the concept of insider/outsider, the autoethnographic approach to narrative, the participant observation qualitative research method, and the relationship between words and images. The relevant bodies of my work highlighted in this paper are the Italian-Canadian immigrant series, including the Good Friday collection, the labour movement/migrant farm workers collection, and the queer-Italian-Canadian project (work in progress).